2021
DOI: 10.1029/2021gl095453
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variability of the Daytime and Nighttime Atmospheric Turbulence Experienced by InSight on Mars

Abstract: Mars is prone to atmospheric turbulence. Its thin, nearly cloudless atmosphere and low surface thermal inertia entail strong near-surface unstable temperature gradients, resulting in convective turbulencecells, plumes, vortices-at daytime in the planetary boundary layer (PBL;Larsen et al., 2002;Petrosyan et al., 2011;Tillman et al., 1994). This induces a wealth of daytime high-frequency variations in the atmospheric pressure, wind and temperature measured by landers and rovers (Martínez et al., 2017 for a revi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
63
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(81 citation statements)
references
References 39 publications
15
63
0
Order By: Relevance
“…The Mars Environmental Dynamics Analyzer (MEDA 21 ) instrument on Perseverance and the meteorological suites of previously landed missions 20 , 22 typically measure pressure, temperature and wind fluctuations with sampling frequencies of 0.1 Hz to 10 Hz. These instruments study the turbulence variability 23 , 24 and the Martian turbulent energy cascade 1 , 17 , 25 .…”
Section: Atmospheric Turbulencementioning
confidence: 99%
See 1 more Smart Citation
“…The Mars Environmental Dynamics Analyzer (MEDA 21 ) instrument on Perseverance and the meteorological suites of previously landed missions 20 , 22 typically measure pressure, temperature and wind fluctuations with sampling frequencies of 0.1 Hz to 10 Hz. These instruments study the turbulence variability 23 , 24 and the Martian turbulent energy cascade 1 , 17 , 25 .…”
Section: Atmospheric Turbulencementioning
confidence: 99%
“…This can be owing to the flow-induced turbulence from the rover/mast itself but also to the direct sensing of the incoming flow fluctuations, seen to be the dominant factor for outdoor microphones in other studies 6 . Moreover, the daytime local turbulence is known to increase for larger ambient wind speeds 24 . The high microphone sampling rate provides an opportunity to observe very intense but short wind gusts, on a timescale of 10 s. In Fig.…”
Section: Atmospheric Turbulencementioning
confidence: 99%
“…One plausible explanation for this GW source is the nocturnal jet and its induced shear instability found in the Martian tropical region (Chatain et al., 2021; Joshi et al., 1997; Savijärvi, 2012). It is suggested that the nighttime burst of local turbulence experienced by InSight during the dusty season is the strong development of the nocturnal low‐level jet in dustier conditions (Chatain et al., 2021). However, the vertical extent of the jet and its upper level of dynamical influence still need validation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may not be the leading cause for the strong nighttime Mp‐layer GWs as the convection at night reaches its minimum. One plausible explanation for this GW source is the nocturnal jet and its induced shear instability found in the Martian tropical region (Chatain et al., 2021; Joshi et al., 1997; Savijärvi, 2012). It is suggested that the nighttime burst of local turbulence experienced by InSight during the dusty season is the strong development of the nocturnal low‐level jet in dustier conditions (Chatain et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a fascinating possibility is that the mechanism depicted by Wu et al. (2021) could explain the observed strong enhancement of vortex‐induced pressure drops during the “dusty” season by both Curiosity (Ordonez‐Etxeberria et al., 2018; Newman et al., 2019) and InSight (Chatain et al., 2021). On this topic, the future in situ atmospheric measurements by Perseverance and Zhurong, at different locations than Curiosity and InSight, will be particularly interesting.…”
Section: Figurementioning
confidence: 99%